HUBUNGAN SIKAP SOSIAL DAN KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR DI WILAYAH KECAMATAN GUMELAR DI TINJAU DARI GENDER - Armo Armo; Akhmad Jazuli; Tukiran Tanireja (Universitas Muhammadiyah Purwokerto, 2019)
This study aims to determine the relationship between (1) social attitudes andlearning achievements of fifth grade elementary school students in the NagawiruCluster Gumelar District; (2) emotional intelligence with learning achievement of fifthgrade elementary school students; and (3) social attitudes and emotional intelligence offifth grade elementary school students.This research used a correlational research witha quantitative approach. The variables in this study are emotional intelligence, socialattitudes, and student achievement. The study population was all fifth grade students inelementary schools in the Nagawiru cluster. The number of samples taken was 75students by using proportional random sampling technique. Data collection techniquesusing questionnaires and documentary studies. The analysis technique used is theproduct moment correlation technique and multiple regression. The results showed that(1) there was a positive and significant relationship between social attitudes with classV student achievement Whereas female students have a positive and significantrelationship between social attitudes and learning achievements ; (2) there a positiveand significant relationship between emotional intelligence and student achievemenespecially females; and (3) there is a positive and significant relationship betweensocial attitudes and emotional intelligence. Meanwhile, both male and female studentshave social attitudes with emotional intelligence with low and moderate categories.